Polarization-singular structure in laser images of phase-inhomogeneous layers to diagnose and classify their optical properties - Ushenko, Yu.O.; Misevich, I.Z.; Angelsky, A.P.; Bachinsky, V.T.; Telen’ga, O.Yu.; Olar, O.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Adduced in this work are the results of investigation aimed at analysis of coordinate distributions for azimuths and ellipticity of polarization (polarization maps) in laser images of three types of phase-inhomogeneous layers (PhIL), namely: rough, ground and bulk scattering layers. To characterize polarization maps for all the types of PhIL, the authors have offered to use three groups of parameters: statistical moments of the first to fourth orders, autocorrelation functions, logarithmic dependences for power spectra related to distributions of azimuths and ellipticity of polarization inherent to PhIL laser images. Ascertained are the criteria for diagnostics and classification of PhIL optical properties.